PENGARUH MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN FLASHCARD TERHADAP KEMAMPUAN MEMBACA SISWA KELAS 1 SEKOLAH DASAR - Riski, Via; Ida Zulaeha; Panca Dewi Purwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the Teams Games Tournament (TGT) model assisted by flashcards on the reading ability of first-grade elementary school students. The research employed a quantitative approach with a pretest-posttest one-group design. The sample consisted of 17 respondents using a saturated sampling technique. The prerequisite test conducted was the normality test using the Kolmogorov-Smirnov formula, with data considered normally distributed at a significance level of 5% (0.05). Hypothesis testing was conducted using a one-sample t-test. Data collection in this study was carried out through tests. The results indicated that the use of the TGT model assisted by flashcards significantly influenced students' reading ability. This was evidenced by the paired sample t-test results, which showed a Sig. (2-tailed) value of 0.0000227, smaller than 0.05, and the calculated t-value (t_calculated) of -5.8916776, which was greater than the critical t-value (t_table) of 2.1199053. Therefore, it can be concluded that the use of the TGT learning model positively impacts the reading ability of first-grade students in Indonesian language lessons at SDN 2 Kaliwenang.